The shock of the news: media coverage and the making of 9/11 - Monahan, Brian A. (New York University Press, 2010)
Introduction : understanding public drama -- News as public drama : the era of the endless news cycle -- Making public drama : telling a good story -- Framing September 11 : overview of media and audience response -- Seeking sense amid the shock : the coverage on September 11 -- What has been and what will be : dramatic amplification at ground zero -- This is your story, too : cultivating emotionality at ground zero -- America's heroes : New York firefighters in the spotlight -- To the stars go the spoils : moral currency and the FDNY -- September 11 and beyond : public drama in the twenty-first century